If I Stay: Where She Went - Book 2 - Forman, Gayle (New York Dutton Books, 2011)
Adam, now a rising rock star, and Mia, a successful cellist, reunite in New York and reconnect after the horrific events that tore them apart when Mia almost died in a car accident three years earlier.
Keywords: Interpersonal relations -- Juvenile fiction; Emotional problems of teenagers -- Juvenile fiction; Rock music -- Juvenile fiction; Musicians -- Juvenile fiction; Interpersonal relations -- Fiction; Emotional problems -- Fiction; Rock music -- Fiction; Musicians -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction